INOVASI KURIKULUM MELALUI MODEL CASE STUDY BERBASIS EDUCULTURE TERHADAP KEMAMPUAN PSIKOPEDAGOGI MAHASISWA PGSD PADA MATA KULIAH PERKEMBANGAN PESERTA DIDIK - Siti Raihan; Andi Dewi Riang Tati; Rahmawati Patta; Rahmat; Muh. Rizah Putrawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Teacher education programs must equip prospective elementary school teachers with strong psychopedagogical competencies, particularly in understanding child development, demonstrating empathy, and responding to diverse socio-cultural learning contexts. However, many first-semester PGSD students still show limitations in analytical reasoning, cultural sensitivity, and contextual pedagogical reflection. This study aims to examine the effect of an Outcome-Based Education (OBE) curriculum innovation through an educulture-based case study model on the psychopedagogical competencies of first-semester PGSD students in the Child Development course. This research employed a quasi-experimental design with a pretest–posttest control group involving 60 students (n=30 experimental, n=30 control). The experimental class received learning through case studies embedded with local cultural contexts, while the control class experienced conventional instruction. Data collection used case-based written tests, observation sheets, and student response questionnaires. Data were analyzed using descriptive statistics and independent sample t-tests. The results showed a significant improvement in the experimental group compared to the control group, indicated by higher posttest scores and a large N-gain category. Students in the experimental group demonstrated better analytical thinking, increased cultural sensitivity, and stronger pedagogical reflection. These findings indicate that the OBE-based educulture case study model is effective in strengthening the psychopedagogical competencies of PGSD students. This approach is recommended for teacher education programs to enhance authentic, contextual, and culturally responsive learning experiences.